Kinetics of enzyme action : - Stein, Ross L. (John Wiley, 2011)
"Few scientists have the knowledge to perform the studies that are necessary to discover and characterize enzyme inhibitors, despite the vested interest the pharmaceutical industry has in this field. Beginning with the most basic principles pertaining to simple, one-substrate enzyme reactions and their inhibitors, and progressing to a thorough treatment of two-substrate enzymes, Kinetics of Enzyme Action: Essential Principles for Drug Hunters provides biochemists, medicinal chemists, and pharmaceutical scientists with numerous case study examples to outline the tools and techniques necessary to perform, understand, and interpret detailed kinetic studies for drug discovery"--Provided by publisher.